Genetic diversity of almond rootstocks. The INRA Prunus rootstock breeding program - Duval H. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
Almond and peach seedlings and peach*almond hybrids are still the most grown almond rootstocks in the Mediterranean countries. However a lot of new almond rootstocks were released in the last years, with different vigour, disease and nematode resistance, tolerance to abiotic stress. The almond rootstock choose is become more important, but there are opportunities for new rootstocks adapted to certain soil types like heavy soils or adapted to new high density systems. It could be possible to create them by interspecific crosses between several Prunus species, checking first the graft-compatibility with almond varieties. The main objective of the Breeding rootstock program is to pyramide three root-knot nematode resistance genes by interspecific crosses almond*peach*myrobalan.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)